Correlations of plasma kynurenines with CSF levels, and their relation to markers of Alzheimer's disease pathology, diagnostic phases and cognitive performance: Biomarkers (non‐neuroimaging)/Novel biomarkers. (7th December 2020) - Bakker, Lieke; Koehler, Sebastian; Choe, Kyonghwan; van den Hove, Daniel L.A.; Kenis, Gunter; Eussen, Simone J.P.M.; Ueland, Per M.; Verhey, Frans R.J.; Ramakers, Inez H.G.B.
Abstract: Background: Finding novel biomarkers for Alzheimer's disease (AD) for prediction, diagnosis or disease monitoring is a key research area. The kynurenine pathway(KP) consists of different metabolites of the essential amino acid tryptophan that have putative neurotoxic and ‐protective properties such as NMDA‐receptor agonism or potent antioxidation. Small clinical studies have shown altered levels in blood plasma and cerebrospinal fluid(CSF) in AD and other neurodegenerative diseases. However, whether peripheral kynurenine concentrations in plasma resemble those found in CSF is still largely unknown. The present study aims to investigate whether kynurenine concentrations in plasma correlate with those measured in CSF, and to study the role of kynurenines as biomarkers for AD. Method: This study uses baseline data from 800 participants obtained in the Biobank Alzheimer Centrum Limburg(BBACL) study, an ongoing prospective cohort study in patients of the memory clinic of the Maastricht University Medical Center, the Netherlands. Blood plasma and CSF concentrations (CSF available for 151 participants) of tryptophan, kynurenine, kynurenic acid, 3‐hydroxykynurenine, xanthurenic acid, anthranilic acid, 3‐hydroxy anthranilic acid, quinolinic acid and picolinic acid were determined by means of liquid chromatography‐tandem mass spectrometry. Additionally, Ab1‐42, total‐tau and phosphorylated tau in CSF were determined using commercially available single‐parameter ELISA methods. Correlational and multiple linear regression analyses studied associations between plasma and CSF kynurenine levels, associations of CSF kynurenine concentrations with AD pathological markers, differences in plasma and CSF kynurenine levels in different diagnostic phases (subjective cognitive decline, mild cognitive impairment, dementia) and their associations with cognitive performance. Result: Plasma concentrations of tryptophan (r = .43, p <0.001) and KP metabolites kynurenine (r = .42, p <0.001), 3‐hydroxykynurenine (r = .37, p <0.001), kynurenic acid (r = .32, p <0.001), anthranilic acid (r = .59, p <0.001), quinolinic acid (r = .67, p <0.001) and picolinic acid (r = .76, p <0.001) significantly correlated moderately to high with their corresponding CSF concentrations. Associations with Ab1‐42, t‐tau and p‐tau, disease stages and neuropsychological test scores are currently being analyzed and will be presented. Conclusion: From a diagnostic viewpoint these results are promising, as the collection of plasma samples is less invasive compared to CSF.